Consumer Loyality Analysis in Terms of Product Quality and Brand Image of PT. Indojaya Agrinusa Medan Products - Noferman Gea (Program Pascasarjana STIE Amkop Makassar, 2026)
This study aims to analyze the influence of product quality and brand image on customer loyalty towards broiler chicken feed products at PT. Indojaya Agrinusa Medan. This study uses a quantitative approach with a survey method. The sampling technique applied is non-probability sampling with purposive sampling, where respondents are consumers of broiler chicken feed products at PT. Indojaya Agrinusa Medan. The collected data were analyzed using path analysis with the help of the SPSS program to examine the relationship between variables and test the research hypothesis. The results show that product quality and brand image have a significant influence on customer loyalty. High product quality and a positive brand image can build consumer trust and encourage repeat purchases. Therefore, companies need to maintain and improve product quality while strengthening their brand image to maintain customer loyalty. Future research is recommended to include additional variables that may influence customer loyalty to obtain more comprehensive findings.